El biotipo B de Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) adquiere mayor importancia en el Valle del Cauca = The B biotype of Bemisia tabaci (Homoptera: Aleyrodidae) becomes more important in the Cauca Valley - Rodríguez Torres, Isaura Viviana; Morales, H; Bueno Mondragon, J.M.; Cardona Mejía, César (2005)
To update information on whitefly species composition and occurrence of whitefly biotypes affecting annual crops in the Cauca Valley of Colombia, a new survey was coriducted in 2002-2003. Thirty-seven sites in 23 differerit locations were visited. Adult and pupal samples were taken from 11 crops. Differentiation between the species Ilemisia tabaci (Gennadius) and frialeurodes vaporariorurn (Westwood) was based on morphological characteristics of the pupae. Reconfirmation of species identity and differentiation between biotypes A and B was done by means of random amplified polymorphic DNA (RAI D s-PCR analysis). T. uaporariorum, the predominant species in 1997 (present iii 73% of the samples), now occupies a secondary place detected in only 22,7% of the samples. The Biotype A of B. tabaci (15,5% of the samples in 1997) was not found in any samples taken in 2002 2003 On the contrary the incidence of the B biotype increased from 11 S% in 1997 to 62 6% in 2003 Increased incidence of the B biotype was also evidenced by the common occurrence of such physiological disorders as irregular ripening of tomatoes, silver-leaf symptoms on squash and pod chlorosis on snap beans. These disorders had not been recorded in the Cauca Valley before. Snap beans, soybeans, pepper. sweet potato, and grapes were recorded as new host planta for the ¡3 biotype. A mix of T vaporariorum and biotype B was found in 14,6% of the samples The B biotype showed high levels of resistance to conventional insecticides and susceptibility to novel insecticides (neonicotinoids and insect growth regulators) The importance that these changes in species composition and biotypes of whitefly have to the regions agriculture are discussed.